Ultrafast photoinduced structure phase transition in antimony single crystals - Fausti, Daniele; Misochko, Oleg V.; Van Loosdrecht, Paul H. M. (Physical Review B - Condensed Matter and Materials Physics, 2009)
Picosecond Raman scattering is used to study the photoinduced ultrafast dynamics in Peierls distorted antimony. We find evidence for an ultrafast nonthermal reversible structural phase transition. Most surprisingly, we find evidence that this transition evolves toward a lower symmetry in contrast to the commonly accepted rhombohedral-to-simple cubic transition path. Our study demonstrates the feasibility of ultrafast Raman scattering symmetry analysis of photoinduced nonthermal transient phases. © 2009 The American Physical Society.
CRIS-Team Scopus Importer:2022-07-20